Resilient hepatic mitochondrial function and lack of iNOS dependence in diet-induced insulin resistance - Kakimoto, Pamela; Chausse de Freitas, Bruno (PLOS ONE, 2019)
Obesity-derived inflammation and metabolic dysfunction has been related to the activity of the inducible nitric oxide synthase (iNOS). To understand the interrelation between metabolism, obesity and NO., we evaluated the effects of obesity-induced NO. signaling on liver mitochondrial function. We used mouse strains containing mitochondrial nicotinamide transhydrogenase activity, while prior studies involved a spontaneous mutant of this enzyme, and are, therefore, more prone to oxidative imbalance. Wild-type and iNOS knockout mice were fed a high fat diet for 2, 4 or 8 weeks. iNOS knockout did not protect against diet-induced metabolic changes. However, the diet decreased fatty-acid oxidation capacity in liver mitochondria at 4 weeks in both wild-type and knockout groups; this was recovered at 8 weeks. Interestingly, other mitochondrial functional parameters were unchanged, despite significant modifications in insulin resistance in wild type and iNOS knockout animals. Overall, we found two surprising features of obesity-induced metabolic dysfunction: (i) iNOS does not have an essential role in obesity-induced insulin resistance under all experimental conditions and (ii) liver mitochondria are resilient to functional changes in obesity-induced metabolic dysfunction.